2010
DOI: 10.5171/2010.592297
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Customer Loyalty of Using Internet Banking in Malaysia

Abstract: Internet banking (IB) has become one of the widely used banking services among Malaysian retail banking customers in recent years. Despite its attractiveness, customer loyalty towards Internet banking website has become an issue due to stiff competition among the banks in Malaysia. As the development and validation of a customer loyalty model in Internet banking website context in Malaysia had not been addressed by past studies, this study attempts to develop a model based on the usage of Information System, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 65 publications
4
50
0
3
Order By: Relevance
“…Thus, the study concluded that, increasing the trust the customers have toward their internet banking providers, providing satisfactory services, gaining their commitment and building a strong bank reputation enhances the loyalty of the customer towards their internet banking services providers within the Nigerian context. This conclusion is in accordance with previous findings [10,29,17,23,53,33,43,42]. In addition, the results reveal that the odd of a customer being loyal to his/her internet banking service providers is higher with the bank reputation as compared to customer satisfaction, trust, and commitment in the Nigerian context.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Thus, the study concluded that, increasing the trust the customers have toward their internet banking providers, providing satisfactory services, gaining their commitment and building a strong bank reputation enhances the loyalty of the customer towards their internet banking services providers within the Nigerian context. This conclusion is in accordance with previous findings [10,29,17,23,53,33,43,42]. In addition, the results reveal that the odd of a customer being loyal to his/her internet banking service providers is higher with the bank reputation as compared to customer satisfaction, trust, and commitment in the Nigerian context.…”
Section: Resultssupporting
confidence: 82%
“…In addition, the results reveal that the odd of a customer being loyal to his/her internet banking service providers is higher with the bank reputation as compared to customer satisfaction, trust, and commitment in the Nigerian context. This conclusion is consistent findings of [53] who found reputation to be an essential factor for encouraging customer loyalty towards Internet banking in Malaysia.…”
Section: Resultssupporting
confidence: 80%
“…According to Yee and Faziharudean (2010) perceived value or accepted value has contribution to customer loyalty. H4: there is a positive and significant relationship between perceived value and customer loyalty.…”
Section: Perceived Valuementioning
confidence: 99%
“…Lowering perceived risks associated with online transactions as well as maintaining transaction trust is vital keys to attracting and retaining customers [7]. The quality elements of the e-service are expected to affect e-trust directly [8], because they represent trust cues that convey the trustworthiness of the site and the system to customers [9].The authors in [10] found that trust, habit and reputation have a significant influence on customer loyalty towards individual Internet banking websites, and in an investigation by [11] service quality, e-satisfaction, and e-trust have a strong direct effect on e-loyalty. The authors in [12] also investigated trust and switching costs as a way to build e-loyalty in Internet markets.…”
Section: Literature Reviewmentioning
confidence: 99%